The Stages of the Healthcare System Reform of the Republic of Kazakhstan (Farabi Journal of Social Sciences, 2019)
Abstract. The article gives a historical and legal analysis of formation and development of the health system of theRepublic of Kazakhstan. State puts healthcare to the level of the priority directions of the national policy. Duringthe years of independence adopted a number of state programmes, implementation of which determines the mainachievements in the sphere of public health. The article presents a critical analysis of policy documents, which formedthe basis for the establishment of a modern health system in Kazakhstan. The direction of the current stage and theproblems are also identified challenges to the state to achieve their goals.